Project Based Learning (PjBL) and Gender Roles: Impact on Creativity and Environmental Literacy - Zahro, Firda Fitriani; Anggoro, Bambang Sri; Ulfa Nabila, Siti (Universitas Wiralodra, 2025)
The ability to think creatively and environmental literacy of students in mathematics learning is a skill that needs to be mastered by students. The purpose of this research is to examine the influence of the PjBL learning model on creative thinking skills and environmental literacy, considering gender differences. This research is a quantitative study of the Quasi-Experimental Design type where in this study there are two classes, namely the experimental class which will use the PjBL learning model and the control class with the expository learning model. The subjects of this research are eighth-grade students at SMP IT Budi Luhur, with a total population of 58 students. The sample in this study is class VIII A as the experimental class and class VIII B as the control class using the expository model. The data collection techniques were in the form of tests and observations. Hypothesis testing in this study used a two-way Manova test. (Two way manova). the results of the research and discussion concluded that the ability to think creatively and environmental literacy using the PjBL learning model is better compared to using the expository learning model.